2015
DOI: 10.1016/j.theriogenology.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

In vitro bovine embryo production in a synthetic medium: Embryo development, cryosurvival, and establishment of pregnancy

Abstract: a b s t r a c tThe aim of this study was to develop an in vitro embryo culture medium without either fetal calf serum or BSA, using various growth factors and cytokines (GFs-CYKs; IGF-I, IGF-II, bFGF, LIF, GM-CSF, TGF-b1, and PDGF-BB), and other molecules with surfactant and embryotrophic properties, such as recombinant albumin (RA) and hyaluronan (HA). The first part of the study was dedicated to define the best combination of GFs-CYKs þ RA þ HA for optimal embryonic development. Next, we compared development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
0
13
1
Order By: Relevance
“…The embryo will be dividing rapidly at this time and by day seven the embryo will be ready for transfer (Moreno et. al, 2015).…”
Section: In Vitro Embryo Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The embryo will be dividing rapidly at this time and by day seven the embryo will be ready for transfer (Moreno et. al, 2015).…”
Section: In Vitro Embryo Productionmentioning
confidence: 99%
“…To transfer an embryo a catheter containing the embryos is inserted into the vagina, through the cervix, and up into the uterus. Pregnancy occurs and is successful if an embryo sticks and is implanted in the lining of the uterus and grows (Moreno et. al, 2015).…”
Section: In Vitro Embryo Productionmentioning
confidence: 99%
“…There have been several attempts to remove BSA from IVP systems to develop chemically defined media. The defined culture media are usually supplemented with polyvinyl alcohol (PVA), which provides a surfactant activity similar to albumin, and other molecules with embryotrophic properties such as growth factors or cytokines [7,8]. Based on the similarities between porcine embryonic cells and stem cells, Spate et al [9] recently successfully replaced the BSA in embryo culture medium with 5-(4chloro-phenyl)-3-phenyl-pent-2-enoic acid (PS48), an stimulant of the Warburg Effectlike metabolism [9] increasing outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been acknowledged that multiple types of receptors expressed on the surface of the embryo play a key role in embryonic early development [3, 4], for example, growth factor receptors (GFRs), cytokine receptors (CRs) and hormone receptors (HRs) [57]. Furthermore, animal experiments showed that co-cultured with agonists or ligands of receptor tyrosine kinases (RTKs), including epidermal growth factor (EGF), colony stimulating factor (CSF), insulin like growth factor-1 (IGF-1) and so on, could remarkably promote embryo development and improve embryo quality [812]. Whereas, inhibition of RTKs function would weaken embryo growth ability resulting in arrest of development and even embryo degeneration [1317].…”
Section: Introductionmentioning
confidence: 99%